Major depression amid financial crisis in Greece: Will unemployment narrow existing gender differences in the prevalence of the disorder in Greece?. (30th August 2016) - Economou, Marina; Angelopoulos, E.; Peppou, Lily Evangelia; Souliotis, Kyriakos; Stefanis, Costas
Abstract: Rises in unemployment as a corollary to the global economic crisis may impinge on the prevalence of depression disproportionally for the two genders. Therefore, differences in the prevalence of the disorder as a function of gender and age were explored in four nationwide surveys in Greece in 2008, 2009, 2011 and 2013. Results indicate that in 2013, men of productive age had a higher prevalence of major depression than women, in contrast to the epidemiology of the disorder. The psychiatry community should be in tune to future changes in the mental health landscape elicited by the social fermentation processes of the global recession. Highlights: Men of working age outnumber women in the prevalence of depression. The enduring recession may alter existing epidemiology of mental disorders. The impact of unemployment on depression should be explored separately for the two genders.